Effects of Minimum Wage Increases on Teenage Employment: Survey Versus Administrative Data - de Wet van der Westhuizen (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2022)
This paper empirically examines the impact of the 2001 New Zealand minimum wage reform on the employment of 16-17 and 18-19-year-olds using administrative data from Statistics New Zealand's Integrated Data Infrastructure. This reform increased the real minimum wage of 18-19-yearolds by 68%, and 16-17-year-olds by 35% in 2001 and 2002. The impact of the minimum wage reform on employment is estimated in two phases. First, existing New Zealand empirical evidence is reproduced using survey data from the Household Labour Force Survey to test and adopt an identification method which has examined the impact of this reform and is established in the international literature. Second, using this identification method in combination with administrative data, preliminary estimates highlight that the 2001 minimum wage reform had small and positive effects on the employment of teenagers. However, findings must be interpreted with caution due to concerns with a key identification assumption.
Keywords: 330; minimum wage; employment; teenage employment; administrative data; survey data; difference-in-differences